Design issues for directional coupler- and mmi-based optical microring resonator filters on inp - Kalli, Kyriacos; Themistos, Christos; Komodromos, Michael; Rajarajan, Muttukrishnan; Rahman, Bilkish M Azizur; Grattan, Kenneth Thomas Victor (My University, 2004)
The characterization and optimization of optical microring resonator-based optical filters on deeply etched GaInAsP-Inp waveguides, using the finite element-based beam propagation approach is presented here. Design issues for directional coupler- and multimode interference coupler-based devices, such as field evolution, optical power, phase, fabrication tolerance and wavelength dependence have been investigated.
Keywords: Resonators; Optical fibers; Lasers; Fibers